Fecaliths: diagnostic value of this finding in a patient without acute abdomen - Ramírez Chacón, Jorge Luis (2017)
Abstract: Acute apendicitis, a clinical inflammation of the cecal appendix, in which the initial physiopathologic aspect is the obstruction of the lumen of the appendix, is one of the most common diagnosis made in the emergency department, but his clinical diagnosis in the patient with a special condition is not always as simple as it does.  Following, we present the case of a 76-years old female patient with a history of periumbilical abdominal pain of 24 hours of evolution without specific clinical signs of acute apendicitis at the initial evaluation, but during it´s evolution we saw unusual radiologic findings.